PENGARUH DIET KETOGENIK TERHADAP EKSPRESI Ki-67, CASPASE-3, DAN MDA PADA JARINGAN HATI - Harahap, Huntari; Irfannuddin, Irfannuddin; Murti, Krisna (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2018)
Obesity is a problem of global epidemics and arise a health threat to people. The prevalence of obesity in the United States in 2016 was around 39.8% in adults aged 40-59 years and 18.5% in young adults aged 20-39 years. One of the dietary patterns used to overcome obesity is the ketogenic diet. The main metabolic reaction due to the ketogenic diet occurs in the liver which make lesion. The ketogenic diet is a high-fat diet, quite protein, low in carbohydrates (usually less than 50 g / day). The effect of the ketogenic diet on the liver is help maintain TCA cycle homeostasis, prevents the accumulation of intermediate fatty acids that are not oxidized, maintains the redox balance of the liver, and supplies energy to extrahepatic organs in the glucose deficiency stage. The ketogenic diet can reduce cell proliferation which is characterized by a decrease in the percentage of cells in ki-67 positive staining and increase cell apoptosis which is characterized by an increase in caspase-3 positive staining and reduce oxidative stress as assessed by MDA reduction. Key Words : Obesity, Ketogenic Diet, Ki-67, Liver, Caspase-3, MDA